2016
DOI: 10.1101/090928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taming the Late Quaternary phylogeography of the Eurasiatic wild ass through ancient and modern DNA

Abstract: Taxonomic over-splitting of extinct or endangered taxa, due to an incomplete knowledge of both skeletal morphological variability and the geographical ranges of past populations, continues to confuse the link between isolated extant populations and their ancestors. This is particularly problematic with the genus Equus. To more reliably determine the evolution and phylogeographic history of the endangered Asiatic wild ass, we studied the genetic diversity and inter-relationships of both extinct and extant popul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
1
2
0
1
Order By: Relevance
“…These results indicated that there were no genetic or behavioural barriers to subspecies hybridization and that no cryptic subpopulations have formed due to a lack of admixture. This may be due to weak genetic differentiation between the subspecies; we found that only 0.03% of the analysed SNPs were fixed for opposite alleles in the onager and kulan samples, which is consistent with previous findings demonstrating only low genetic divergence between onagers and kulans (Bennett et al, 2017). Species such as the Asiatic wild ass, which show low levels of divergence between subpopulations or subspecies may therefore present good candidates for hybridization as part of genetic management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that there were no genetic or behavioural barriers to subspecies hybridization and that no cryptic subpopulations have formed due to a lack of admixture. This may be due to weak genetic differentiation between the subspecies; we found that only 0.03% of the analysed SNPs were fixed for opposite alleles in the onager and kulan samples, which is consistent with previous findings demonstrating only low genetic divergence between onagers and kulans (Bennett et al, 2017). Species such as the Asiatic wild ass, which show low levels of divergence between subpopulations or subspecies may therefore present good candidates for hybridization as part of genetic management.…”
Section: Discussionsupporting
confidence: 92%
“…Both subspecies are currently classified as endangered by the IUCN and a major conservation concern is the extreme fragmentation and small sizes of remaining wild populations (Bennett et al, 2017; Kaczensky et al, 2018). Furthermore, on the basis of numerous phylogenetic analyses (Geigl & Grange, 2012; Orlando et al, 2009; Vilstrup et al, 2013), some authors advocate a revision of the separate subspecies status of E. h. onager and E. h. kulan and joint management of the remaining populations (Bennett et al, 2017; Oakenfull et al, 2000). The results presented here demonstrate that genetic or behavioural barriers are unlikely to compromise a mixed stock management approach in in situ and ex situ conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Malgré ces incertitudes et limites, l'apport de la paléogénétique basé sur les méthodes de PCR à l'archéologie, la paléoanthropologie, l'archéozoologie et l'archéobotanique a été (et est toujours) multiple et riche. Il a permis de déterminer à quelles lignées maternelles ont appartenu des individus mis au jour dans des sites archéologiques et ainsi de reconstruire des migrations et remplacements de populations humaines (par exemple en Europe centrale au cours des dernières 6 500 années ; Brandt et al, 2013), mais aussi d'animaux domestiqués (par ex : les chats, Ottoni et al, 2017), des relations familiales et sociales au sein des cimetières (par ex : Keyser-Tracqui et al, 2003), identifier des pathogènes et parasites intestinaux (Côté et al, 2016), éclairer les positions phylogénétiques de certains animaux éteints emblématiques (comme le mammouth ; Debruyne et al, 2003) ou énigmatiques (comme l'hydrontin ; Bennett et al, 2017), déterminer les événements initiaux lors de la domestication des animaux (comme les chevaux ; Ludwig et al, 2009), reconstruire le paléoenvironnement grâce à l'analyse de pollens et des sédiments (comme pour le Groenland il y a environ 800 000-450 000 ans ; Willerslev et al, 2007) ou encore étudier la réponse de la mégafaune aux changements climatiques et environnementaux et l'action anthropique (Lorenzen et al, 2011).…”
Section: Les éTudes Paléogénétiquesunclassified
“…While fossils of kiang‐like wild asses are known from Pleistocene deposits in Alaska (Harington, ), the Pleistocene range of kiangs remains unknown. Wild asses during the Pleistocene spanned from present‐day France, where they were known as the European wild ass ( E. hydrintius ), to China (Figure a) in regions south of 50˚ N (Bennett et al, ).…”
Section: Introductionmentioning
confidence: 99%